CONTROLE DE Meloidogyne incognita EM SOJA COM EXTRATO DE Pycnoporus sanguineus: CONTROLEALTERNATIVO DE Meloidogyne incognita - Tasca, Gisela Paula; Brito, Olivia Diuelen Costa; Stangarlin, José Renato; Kuhn, Odair José (Scientia Agraria Paranaensis, 2022)
Meloidogyne incognita is an endoparasitic and sedentary nematode that forms galls on the roots and damage several agricultural crops, including soybean. Its control needs several management methods, including the use of microbial extracts. Thus, the objective of this work was to verify the influence of the fungus Pycnoporus sanguineus extract on the control of M. incognita in soybean. The treatments were concentrations of the crude extract of basidiocarps from P. sanguineus (0%; 2.5%; 5%; 7.5%; and 10%) which were applied to the aerial part of the plants, and after 72 h the nematodes (eggs + second stage juveniles – J2) were inoculated. After 60 days were evaluated fresh and dry masses of the aerial part and height of aerial part, and the nematological parameters number of egg masses, number of galls and total number of nematodes. It was concluded that there was a reduction in total number of nematodes in a dose-dependent manner for crude extract of P. sanguineus, where the calculated value of 17% was the concentration which more reduced de number of nematodes. The vegetative parameters were not influenced, indicating that besides the control of the pathogen in the roots by the treatments on the leaves, this induction of resistance did not produce metabolic fitness to the plant.